Dıdactıc And Methodologıcal Basıs Of The Formatıon Of Research Competence In Vocatıonal Educatıon Teachers - Turmatov Djalolıddın Raxmatullayevıch , Askarov Ikhtıyor Bakhtıyorovıch (International Journal of Advanced Science and Technology, 2020)
This article explores the structure of the research competence of future vocational education teachers, the key factors in improving the traditional didactic provision of research competencies for teachers of vocational education, and the use of interactive teaching methods and tools to improve the research competence methodology of future vocational teachers.